SCREENING OF MAIZE VARIETIES FOR GRAIN YIELD AT DERA ISMAIL KHAN - N. Hussain; M. Y. Khan; M. S. Baloch (Journal of Animal and Plant Sciences, 2011)
In order to evaluate the performance of advanced lines from different research institutions across the country and commercially cultivated varieties, an experiment was conducted at the Agricultural Research Institute, Dera Ismail Khan, Pakistan, during spring 2008. The data were recorded on days to pollen shedding, days to silking, plant height and grain yield. All varieties showed significant differences with each other for all the traits studied. Variety “Ev-5098” had the highest grain yield of 7.35 t ha-1. Variety “Islamabad White” took more days to pollen shedding and silking while variety Soan-3 was found early maturing, which took 69 days to 50% silking. The highest plant height of 205 cm was noted in variety Sahiwal-2002. These varieties had a wide genetic background, thus showing grain yield ranges from 5.26 to 7.35 t ha-1. Maize varieties EV-5098 and Sahiwal-2002 were found most promising, which have the potential to increase the average yield of maize in Dera Ismail Khan and are therefore recommended for general cultivation.
Keywords: Maize; varieties; growth; grain yield; adaptation